Draft Genome Sequence of a Taxonomically Unique Acinetobacter Clinical Strain with Proteolytic and Hemolytic Activities - Traglia, German Matias (2015)
Acinetobacter sp. strain A47, which has been recovered from several soft tissue samples from a patient undergoing reconstructive surgery due to a traumatic amputation, was categorized as a taxonomically unique bacterial strain. The molecular analysis based on three housekeeping protein-coding genes (16S rRNA, rpoB, and gyrB) showed that strain A47 does not belong to any of the hitherto known taxa and may represent a previously undescribed Acinetobacter species.